Fructose metabolism from a functional perspective: Implications for athletes - Tappy, L.; Rosset, R. (Sports Medicine, 2017)
Substantial amounts of fructose are present in our diet. Unlike glucose, this hexose cannot be metabolized by most cells and has first to be converted into glucose, lactate or fatty acids by enterocytes, hepatocytes and kidney proximal tubule cells, which all express specific fructose-metabolizing enzymes. This particular metabolism may then be detrimental in resting, sedentary subjects; however, this may also present some advantages for athletes. First, since fructose and glucose are absorbed through distinct, saturable gut transporters, co-ingestion of glucose and fructose may increase total carbohydrate absorption and oxidation. Second, fructose is largely metabolized into glucose and lactate, resulting in a net local lactate release from splanchnic organs (mostly the liver). This `reverse Cori cycle` may be advantageous by providing lactate as an additional energy substrate to the working muscle. Following exercise, co-ingestion of glucose and fructose mutually enhance their own absorption and storage